Framework for testing Open Quantum Safe for TLS Servers - Joottun, Atish; Peeroo, Poshan; Yerkiah, Kevin; Chutoo, Anwar (My University, 2024)
This research aims to analyse if the TLS servers in Mauritius are correctly implemented for easy mitigation to Quantum Safe Cryptography. Since Quantum Computing is becoming more advance, we need to secure our online activities to prevent malicious actors from leveraging it against us. The framework, which is written in python, is a versatile tool that provide an effective method for countries or organisations to test their own networks. The methodology involves fetching a list of IP addresses corresponding to a country of organisation which will be filtered for open port 443. For faster execution time, we leverage the use of parallel processing. Finally, the filtered IP addresses will be analysed for the TLDR bug anomaly. This rigorous approach allows for an effective method to determine the effectiveness of the servers and assess the level of security against the impending threats of quantum computing. The code for this project is available at GitHub.
Supplemental Materials: https://osf.io/xrnp5/
Keywords: Open Quantum Safe; Quantum Computing; TLS